Career performance progressions of junior and senior elite track and field athletes - Foss, J. L.; Sinex, J. A.; Chapman, R. F. (Journal of Science in Sport and Exercise, 2019)
Purpose: To compare and assess differences in the career performance progressions of elite junior and Olympic track and field athletes. Methods: Annual best performances from top 8 men and women (e.g. finalists) in track and field events at the 2000 World Junior Championships (junior cohort) and the 2000 Olympic Games (Olympic cohort) were examined. Annual bests of these finalists were tracked each year from select groups: sprints (100 m, 200 m), distance (1500 m, 5000 m), jumps (long jump, high jump), throws (discus, shot put). Age of best lifetime performance, age of final posted performance, and improvement from junior-age best to lifetime best performance were compared between groups. Results: Olympic finalists achieved lifetime best performances at later ages than junior finalists [26.0 ± 4.0 years vs. 21.1 ± 3.5 years; age difference 90% CI (3.7-5.2 years), P < 0.001], and this significant age difference between cohorts was found within all four groups. Olympic finalists improved from under-20 best to lifetime best more so than junior finalists [6.1 ± 4.8% vs. 2.5 ± 2.3%; Age difference 90% CI (2.5-4.8%), P < 0.001]. Of 130 junior finalists, 54 did not improve after age 19, while 19 of 128 Olympic finalists posted no improvement after age 19. Conclusion: The data suggest that these two populations have different career performance progressions and challenge the notion that achieving elite success as a junior athlete is a prerequisite for the same success at the senior level.